The Molecular Genetics of Colorectal Cancer, Hereditary Colorectal Cancer Syndromes, and Early-Onset Colorectal Cancer - Vu, Joceline V.; Sommovilla, Joshua (Digestive Disease Interventions, 2022)
While the incidence of colorectal cancer is decreasing for adults older than 50 years, there is a rise in colorectal cancer among individuals younger than 50 (termed early-onset colorectal cancer). This increase is multifactorial and reflects differences in screening, changes in environmental factors, and other influences. In this article, we review the molecular and genetic basis of sporadic colorectal cancer as well as inherited colorectal cancer syndromes. We also summarize the epidemiology of early-onset colorectal cancer and considerations for the treatment of this population of patients.
Keywords: colorectal cancer; cancer genetics; hereditary colorectal cancer syndromes